Simulation in urology to train non‐technical skills in ward rounds. (26th July 2018) - Somasundram, Khevan; Spence, Heather; Colquhoun, Alexandra J.; Mcilhenny, Craig; Biyani, Chandra S.; Jain, Sunjay
Abstract : Objective: To report our experience of an exercise designed to train newly appointed urology trainees in non‐technical skills on ward rounds as a part of a simulation 'boot camp', through a qualitative analysis of participant feedback on the utility of this method of training. Patients and Methods: The simulations took place in a high‐fidelity simulated ward bay. Forty‐eight doctors with formal urology training ranging between 2 and 60 months (mean 19.1 ± 11.6 months) took part. Thirty‐one participants were on a formal urology specialty training pathway. The remaining participants were core (pre‐specialty) surgical trainees. The entry requirement was that participants must be junior‐level urologists, ideally at the beginning of specialty training. Participants individually led a simulated ward round, which was devised using actors to play patients and a simulated 'switchboard' for telephone conversations. Distractions were introduced deliberately for participants to manage an emergent urology‐related scenario. 'Freeze‐frames' were used to 'pause' the ward round, whereby observing consultants provided feedback on performance. After the simulated exercises, a whole‐group structured debriefing took place. Non‐Technical Skills for Surgeons (NOTSS) scores were generated for participants by seven consultant urologists. Participants completed a two‐part feedback form. Part one involved nine questions scored on a Likert scale, and part two required free‐text responses. Results: The mean (±sd ) itemized NOTSS scores for situational awareness, decision‐making, communication and teamwork, and leadership were 3.01 (±0.15), 2.95 (±0.16), 3.05 (±0.19), and 2.98 (±0.15), respectively. From the thematic analysis, participants commented positively on the number of scenarios per participant, the use of actors as patients and real staff, and the use of freeze‐frames for immediate feedback. Residents also provided suggestions for distractions to be considered in the future. Conclusions: This simulated ward round was generally well received by participants, and the obtained feedback provides an insight into how this can be adapted to maximize the benefits for new specialty residents. The mean NOTSS scores indicated that non‐technical skills performances could be improved. This supports our rationale to train non‐technical skills in a safe environment to bolster career transition into positions of greater decision‐making autonomy.